2011
DOI: 10.5194/acp-11-857-2011
|View full text |Cite
|
Sign up to set email alerts
|

Global distributions of methanol and formic acid retrieved for the first time from the IASI/MetOp thermal infrared sounder

Abstract: Abstract. Methanol (CH 3 OH) and formic acid (HCOOH) are among the most abundant volatile organic compounds present in the atmosphere. In this work, we derive the global distributions of these two organic species using for the first time the Infrared Atmospheric Sounding Interferometer (IASI) launched onboard the MetOp-A satellite in 2006. This paper describes the method used and provides a first critical analysis of the retrieved products. The retrieval process follows a two-step approach in which global dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
93
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 119 publications
4
93
0
Order By: Relevance
“…Sources include plant growth, ocean and decomposition of plant matter as well as biomass burning emission Andreae and Merlet, 2001). The principal sink of CH 3 OH is chemical loss due to OH reaction (Heikes et al, 2002) leading to the formation of CO and H 2 CO (Millet et al, 2006;Rinsland et al, 2009;Stavrakou et al, 2011). The lifetime of CH 3 OH in the surface boundary layer is three to six days (Heikes et al, 2002) and between five and ten days on a global scale (Jacob et al, 2005;Stavrakou et al, 2011).…”
Section: Seasonal Variabilities Of Hcn Ch 3 Oh Hcooh and H 2 Comentioning
confidence: 99%
“…Sources include plant growth, ocean and decomposition of plant matter as well as biomass burning emission Andreae and Merlet, 2001). The principal sink of CH 3 OH is chemical loss due to OH reaction (Heikes et al, 2002) leading to the formation of CO and H 2 CO (Millet et al, 2006;Rinsland et al, 2009;Stavrakou et al, 2011). The lifetime of CH 3 OH in the surface boundary layer is three to six days (Heikes et al, 2002) and between five and ten days on a global scale (Jacob et al, 2005;Stavrakou et al, 2011).…”
Section: Seasonal Variabilities Of Hcn Ch 3 Oh Hcooh and H 2 Comentioning
confidence: 99%
“…Due to its large spatial coverage, combined with its low radiometric noise IASI provides twice daily global measurements of key atmospheric species enabling the analysis of species concentrations, global distribution and transport such as O 3 HNO 3 (Wespes et al, 2009). Other reactive species which are retrieved include carbon monoxide (CO) Pommier et al, 2010), methane (CH 4 ) , sulphur dioxide (SO 2 ) (Clarisse et al, 2008), ammonia (NH 3 ) , methanol (CH 3 OH) and formic acid (HCOOH) Razavi et al, 2011). For a full detailed overview of the IASI instrument, its specifications and trace gas species that can be retrieved see Clerbaux et al (2009).…”
Section: The Iasi Instrumentmentioning
confidence: 99%
“…Similarly, Grutter et al used the limb-viewing Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) to retrieve global distributions of formic acid in the upper troposphere and stratosphere [32]. Razavi et al presented global distributions of formic acid retrieved using the nadir-viewing IASI instrument and showed that the retrieved formic acid is correlated with CO during the burning season in Brazil, the Congo, and Southeast Asia [33].…”
Section: Introductionmentioning
confidence: 99%